MEMBANGUN KARAKTER PADA ANAK USIA PRASEKOLAH - Bambang Samsul Arifin (Psympathic : Jurnal Ilmiah Psikologi, 2009)
Preschool children—as we have known—have much potential which could be used as a basis to build up their character, either in family, school, and society. Their potential therefore needs to be nurtured to help them to achieve their potential to the fullest. But daily life nowadays—could bring negative impact on their development. The intensity of meaningful communication in daily conversation between children and their parents—was seen as a major obstacle on this process, which then becoming the main reason behind the unsuccessful learning of moral values, honesty, and manners. This condition then have negative impact on their character—as we have seen today—many children has emotional disturbance, violent, and shows an inappropriate behaviors.From this phenomenon, a couple effective approaches could be used to design an effective learning good program for their character development—which are knowing the good, reasoning the good, feeling the good, and acting the good. From this approaches point of view—altering their behavior and make good manners as habit were seen as the best approaches available, since altering behavior can be very effective way to develop their character and potential to the fullest. Their character behavior would also be affected by the daily basis learning and natural conditioning to make a good behavior as a habit.Character development for children in this case are including personal character which is an accumulation of goodness that will drive individuals to do the right thing, have a strong self consciousness on moral values, become a good member of society, ethical, knows which is right and wrong, and act consistently on Golden Rules. Aside from it, nationhood and citizenship characteristic is need to be developed too—where this trait is the accumulation of the personal goodness and set of moral and culture values such as an obedience to the state authority, laws, responsibility, fairness and active participation on public affairs.